A survey of the Mindanao Institute of Techonology - Molon, Francisca (Perez) 1925- (s.n.], 1963)
This study is consisted of the history and background of the establishment of the Mindanao Institute of Technology, its objectives and philosophy, organization and operation, its goals and achievements and the extent of its effects on the economic and social life of the people living in communities within the vicinity of its site, Cotabato and the surrounding provinces. This also projects the future role of the college in the economic development of Mindanao based on its achievements in the years under the review, its goals and objectives